2018
DOI: 10.1590/abd1806-4841.20187726
|View full text |Cite
|
Sign up to set email alerts
|

Report of 73 cases of cutaneous sporotrichosis in Mexico

Abstract: We report 73 cases of cutaneous sporotrichosis from the Community Dermatology program, at the central and mountain areas of the state of Guerrero, Mexico. A similar number of cases was found between children and adults, mostly peasants and school-age children with rural occupations. Upper limbs were the mostly affected and the predominant clinical form was lymphocutaneous (56.16%). All cultures corresponded to Sporothrix schenckii (sl). Treatment was done with potassium iodide in 54 patients, achieving clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Brazil and Peru. 1 According to report in Brazil, 372 cats, 34 dogs, and 83 humans, were infected between year 2010 and 2016, which 35% of infected cats were dead. 6 In Asia, Sporothrix infection was uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil and Peru. 1 According to report in Brazil, 372 cats, 34 dogs, and 83 humans, were infected between year 2010 and 2016, which 35% of infected cats were dead. 6 In Asia, Sporothrix infection was uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features were frequently fixed-cutaneous (painless, ulcerative-nodular lesion) or lymphocutaneous form. 1 , 2 Hematogenous spreading (bone, lung, CNS) or disseminated form have been reported in immunocompromised host, which can progress to sepsis and multiple organ failures. 3 This was a case report of conjunctival (mucosal) form of sporotrichosis in immunocompetent host which the infection was highly suspected to be transmitted from pet.…”
Section: Introductionmentioning
confidence: 99%
“…Although farmers comprised the majority of the caseload, paediatric cases made a substantial contribution to the epidemiological profile of sporotrichosis in Jilin Province. This compares with epidemiological studies in Brazil, Venezuela, Mexico and Peru (Abancay) which found that children comprised 11%, 34%, 50% and 62% of sporotrichosis cases identified . Despite this, differences in the epidemiological and clinical characteristics of sporotrichosis in paediatric and adult populations have yet to be fully characterised.…”
Section: Introductionmentioning
confidence: 53%
“…This compares with epidemiological studies in Brazil, Venezuela, Mexico and Peru (Abancay) which found that children comprised 11%, 34%, 50% and 62% of sporotrichosis cases identified. 3,7,13,14 Despite this, differences in the epidemiological and clinical characteristics of sporotrichosis in paediatric and adult populations have yet to be fully characterised.…”
Section: Introductionmentioning
confidence: 99%
“…A mountain chain divides the central region “Centro” into the other two regions, which are the small and big coastal areas, “Costa chica” and “Costa Grande”, these are rich in vegetation, with coffee and palm plantations, where cases of paracoccidioidomycosis [9] and chromoblastomycosis [10] have been reported. Nevertheless, as in other areas of the world, mycetoma and sporotrichosis are the most frequent subcutaneous mycoses in Mexico [3] and in Guerrero State [11], making it the country with second or third highest prevalence of these disesases [1,2].…”
Section: Introductionmentioning
confidence: 99%